Production method of circuit board

By setting an improved layer and a copper foil layer on the copper substrate surface of the circuit board, and combining hot pressing and impregnation treatment technology, the problems of poor dielectric loss, difficult to coordinate thermal conductivity and wear resistance of the existing circuit boards are solved, and the performance stability of the circuit board is significantly improved.

CN119893875AActive Publication Date: 2025-04-25JIANGXI LINGDEHUI CIRCUIT CO LTD

Patent Information

Application Number
CN202510099873.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-25
Estimated Expiration
2045-01-22

AI Technical Summary

Technical Problem

The existing circuit boards have poor dielectric loss, difficult to coordinately improve thermal conductivity and wear resistance, and have poor performance stability under high heat and high humidity conditions.

Method used

The improvement layer and the copper foil layer are arranged in sequence on the surface of the copper substrate, and the improvement layer is composed of epoxy resin, a modified filler agent, a nano-titanium dioxide regulator and a curing agent. Sodium citrate solution, chitosan solution and silane coupling agent KH560 are added to the treatment solution to improve the performance of the circuit board through impregnation treatment.

Benefits of technology

The thermal conductivity, dielectric loss and wear resistance of the circuit board are significantly improved, ensuring performance stability under high heat and high humidity conditions, and achieving coordinated performance improvement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of circuit boards, in particular to a production method of a circuit board, which comprises the following steps of: sequentially arranging an improved layer and a copper foil layer on the surface of a copper substrate, and then carrying out hot pressing treatment on the substrate coated with the improved layer and the copper foil layer at the hot pressing temperature of 180 DEG C for 2 hours. In the production of the circuit board, the surface of the copper substrate is matched with the improved layer and the copper foil layer, and the improved layer is formed by coating an improved material obtained by blending epoxy resin, a modified filler, a nano titanium dioxide regulator and a curing agent on the surface of the copper substrate, so that the thermal conductivity, dielectric loss and wear resistance of a product are enhanced; the performance of the product is improved in a balanced and coordinated manner, and the performance stability effect of the product is remarkable under high-heat and high-humidity conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of circuit boards, and in particular to a production method of a circuit board. Background Art

[0002] With the rapid development of electronic technology, the manufacturing process of printed circuit boards (PCBs), which are almost indispensable in electronic products, has also made great progress. The existing industry has higher and higher requirements for printed circuit boards, and printed circuit boards are developing towards multi-layer circuit board technology with high-density wiring interconnection (HDI) technology, which enables PCBs to provide more functions in a smaller space.

[0003] The existing circuit boards have poor dielectric loss during preparation, and the thermal conductivity of the product is difficult to coordinate with the dielectric loss and wear resistance. The performance balance technology of the product is the difficulty of the present invention. In addition, the product performance stability is poor under high heat and high humidity conditions, which limits the product's use efficiency. Summary of the invention

[0004] In view of the defects of the prior art, an object of the present invention is to provide a method for producing a circuit board to solve the problems raised in the above background technology.

[0005] The present invention solves the technical problem by adopting the following technical solution: The present invention provides a method for producing a circuit board, comprising the following steps: Step 1: The surface of the copper substrate is provided with an improved layer and a copper foil layer in sequence, and then the substrate covered with the improved layer and the copper foil layer is subjected to hot pressing at a temperature of 180° C. for 2 hours; The improved layer comprises the following raw materials in parts by weight: 50-55 parts of epoxy resin, 5-8 parts of modified filler, 4-7 parts of nano titanium dioxide regulator, and 4-7 parts of curing agent; The epoxy resin, the modified filler, the nano titanium dioxide regulator and the curing agent are mixed evenly to obtain an improved material, and the improved material is coated on the surface of the copper substrate to form an improved layer; Step 2: 3-5 parts by mass of 5% sodium citrate solution, 2-4 parts by mass of 2% chitosan solution and 1-3 parts by mass of silane coupling agent KH560 are uniformly mixed to obtain a treatment solution; Step 3: The product of step 1 is immersed in a sufficient amount of treatment liquid, the immersion pressure is 10Mpa, the immersion is 1h, and after the immersion is completed, it is dried to obtain the circuit board of the present invention.

[0006] Preferably, the thickness of the improved layer is 80 um; the thickness of the copper foil layer is 20 um; the epoxy resin is a mixture of bisphenol A epoxy resin and phenolic epoxy resin in a weight ratio of 2:1; and the curing agent is 2-phenylimidazole.

[0007] Preferably, the preparation method of the modified filler is: S01: silane coupling agent KH550, ethanol and water are mixed in a weight ratio of 2:5:1 to obtain a silane solution; 2-4 parts of modified boron nitride whiskers, 3-5 parts of silane solution and 1-3 parts of urea solution are mixed to obtain a modified solution; S02: preheating the nano-attapulgite at 62-66° C. for 1 hour, and then stirring the preheated nano-attapulgite in a modification liquid that is 3-5 times the total amount of the preheated nano-attapulgite for modification treatment, and completing the stirring to obtain modified nano-attapulgite; S03: 3-5 parts of glass fiber, 2-3 parts of cerium oxide and 4-7 parts of sodium silicate solution are stirred and mixed thoroughly, then filtered and dried, and then calcined at 150-170°C for 1 hour. After the calcination is completed, a filler additive is obtained; S04: The modified nano-attapulgite and the filler additive are mixed and ball-milled in a weight ratio of 5:3. After the ball-milling is completed, the mixture is filtered and dried to obtain a modified filler.

[0008] Preferably, the mass fraction of the urea solution is 2-5%; the stirring speed of the stirring modification treatment is 450-550 r / min, and the stirring is for 1 hour.

[0009] Preferably, the mass fraction of the sodium silicate solution is 3-6%.

[0010] Preferably, the preparation method of the modified boron nitride whisker is: 4-7 parts of boron nitride whiskers and 1-3 parts of nano-silica sol are added to 5-8 parts of sodium lignin sulfonate solution, followed by adding 2-3 parts of silicon carbide powder and 1-3 parts of lanthanum oxide, and then mixing and ball milling. After the ball milling is completed, the modified boron nitride whiskers are obtained by suction filtration and drying.

[0011] Preferably, the mass fraction of the sodium lignin sulfonate solution is 2-5%; the ball milling speed of the mixing ball milling treatment is 1050-1150r / min, and the ball milling is for 1h.

[0012] Preferably, the preparation method of the nano titanium dioxide regulator is: S101: Mix nano titanium dioxide in a sufficient amount of potassium permanganate solution and mix well, then wash, filter and dry; S102: stirring and adjusting the dried nano titanium dioxide and the adjusting liquid in a weight ratio of 2:5, filtering and drying after the stirring is completed, to obtain a nano titanium dioxide adjusting agent; The preparation method of the regulating solution is as follows: 2-4 parts of hydroxyapatite, 1-3 parts of alginate, and 1-2 parts of calcium stearate are added to 3-6 parts of 5% by mass sodium dodecylbenzene sulfonate solution and stirred evenly to obtain the regulating solution.

[0013] Preferably, the stirring speed of the stirring adjustment treatment is 550-750 r / min, and the stirring is for 1 hour.

[0014] Preferably, the mass fraction of the potassium permanganate solution is 5-7%.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The circuit board of the present invention is made of a copper substrate surface with an improved layer and a copper foil layer in production, and the improved layer is prepared by mixing epoxy resin, modified filler, nano titanium dioxide regulator and curing agent to obtain an improved material, which is then coated on the surface of the copper substrate to form an improved layer, thereby enhancing the thermal conductivity, dielectric loss and wear resistance of the product, improving the performance balance and coordination of the product, and significantly improving the performance stability of the product under high heat and high humidity conditions; the modified filler is nano attapulgite, which is preheated at 62-66°C for 1h, and then modified by stirring with a modified liquid, and the modified liquid is silane coupling agent K H550, ethanol and water are mixed in a weight ratio of 2:5:1 to obtain silane liquid; then, modified boron nitride whiskers, silane liquid and urea solution are evenly mixed, and the interface of the system raw materials is optimized by the silane liquid. At the same time, the modified boron nitride whiskers are distributed in the system, and the urea solution is used to enhance the coordination effect between the raw materials. At the same time, the modified boron nitride whiskers are subjected to ball milling treatment after being mixed with boron nitride whiskers, nano-silica sol and sodium lignin sulfonate solution, silicon carbide powder and lanthanum oxide. The whiskers are used as the matrix, and the synergistic effect of raw materials such as silicon carbide powder and lanthanum oxide is improved to enhance the whiskers in the system with the nano-concave-convex surface. The improvement effect of rod clay and filler additives, so that the performance of the product is further improved; the filler additive is made by stirring and mixing glass fiber, cerium oxide and sodium silicate solution, then filtering, drying, and calcining at 150-170°C for 1h to obtain the filler additive, and the synergistic effect between the raw materials is adopted to reinforce the system, thereby improving the coordination and stability of the system performance, so that the performance of the product is further improved; the nano titanium dioxide regulator adopts nano titanium dioxide and is stirred evenly in potassium permanganate solution to optimize its active efficiency, and then adjusted and improved by adjusting the adjusting liquid, and the adjusting agent is adjusted. The hydroxyapatite, alginate, calcium stearate and 5% by mass sodium dodecylbenzene sulfonate solution in the solution-saving agent are co-blended. Through the mutual matching and coordination between the raw materials, the synergistic effect of the nano titanium dioxide regulator and the modified filler is optimized, so that the performance of the product is further improved. At the same time, the product of step one is treated with a treatment solution prepared by sodium citrate solution, 2% by mass chitosan solution and silane coupling agent KH560, thereby enhancing the interface improvement effect of the copper foil layer, the improved layer and the copper substrate, and the performance stability of the circuit board is further improved. DETAILED DESCRIPTION

[0016] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0017] A method for producing a circuit board in this embodiment includes the following steps: Step 1: The surface of the copper substrate is provided with an improved layer and a copper foil layer in sequence, and then the substrate covered with the improved layer and the copper foil layer is subjected to hot pressing at a temperature of 180° C. for 2 hours; The improved layer comprises the following raw materials in parts by weight: 50-55 parts of epoxy resin, 5-8 parts of modified filler, 4-7 parts of nano titanium dioxide regulator, and 4-7 parts of curing agent; The epoxy resin, the modified filler, the nano titanium dioxide regulator and the curing agent are mixed evenly to obtain an improved material, and the improved material is coated on the surface of the copper substrate to form an improved layer; Step 2: 3-5 parts by mass of 5% sodium citrate solution, 2-4 parts by mass of 2% chitosan solution and 1-3 parts by mass of silane coupling agent KH560 are uniformly mixed to obtain a treatment solution; Step 3: The product of step 1 is immersed in a sufficient amount of treatment liquid, the immersion pressure is 10Mpa, the immersion is 1h, and after the immersion is completed, it is dried to obtain the circuit board of the present invention.

[0018] The thickness of the improved layer of this embodiment is 80um; the thickness of the copper foil layer is 20um; the epoxy resin is a mixture of bisphenol A epoxy resin and phenolic epoxy resin in a weight ratio of 2:1; and the curing agent is 2-phenylimidazole.

[0019] The preparation method of the modified filler of this embodiment is: S01: silane coupling agent KH550, ethanol and water are mixed in a weight ratio of 2:5:1 to obtain a silane solution; 2-4 parts of modified boron nitride whiskers, 3-5 parts of silane solution and 1-3 parts of urea solution are mixed to obtain a modified solution; S02: preheating the nano-attapulgite at 62-66° C. for 1 hour, and then stirring the preheated nano-attapulgite in a modification liquid that is 3-5 times the total amount of the preheated nano-attapulgite for modification treatment, and completing the stirring to obtain modified nano-attapulgite; S03: 3-5 parts of glass fiber, 2-3 parts of cerium oxide and 4-7 parts of sodium silicate solution are stirred and mixed thoroughly, then filtered and dried, and then calcined at 150-170°C for 1 hour. After the calcination is completed, a filler additive is obtained; S04: The modified nano-attapulgite and the filler additive are mixed and ball-milled in a weight ratio of 5:3. After the ball-milling is completed, the mixture is filtered and dried to obtain a modified filler.

[0020] The mass fraction of the urea solution in this embodiment is 2-5%; the stirring speed of the stirring modification treatment is 450-550 r / min, and the stirring is for 1 hour.

[0021] The mass fraction of the sodium silicate solution in this embodiment is 3-6%.

[0022] The preparation method of the modified boron nitride whisker of this embodiment is: 4-7 parts of boron nitride whiskers and 1-3 parts of nano-silica sol are added to 5-8 parts of sodium lignin sulfonate solution, followed by adding 2-3 parts of silicon carbide powder and 1-3 parts of lanthanum oxide, and then mixing and ball milling. After the ball milling is completed, the modified boron nitride whiskers are obtained by suction filtration and drying.

[0023] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 2-5%; the ball milling speed of the mixing ball milling treatment is 1050-1150r / min, and the ball milling is for 1h.

[0024] The preparation method of the nano titanium dioxide regulator of this embodiment is: S101: Mix nano titanium dioxide in a sufficient amount of potassium permanganate solution and mix well, then wash, filter and dry; S102: stirring and adjusting the dried nano titanium dioxide and the adjusting liquid in a weight ratio of 2:5, filtering and drying after the stirring is completed, to obtain a nano titanium dioxide adjusting agent; The preparation method of the regulating solution is as follows: 2-4 parts of hydroxyapatite, 1-3 parts of alginate, and 1-2 parts of calcium stearate are added to 3-6 parts of 5% by mass sodium dodecylbenzene sulfonate solution and stirred evenly to obtain the regulating solution.

[0025] The stirring speed of the stirring adjustment process in this embodiment is 550-750 r / min, and the stirring is for 1 hour.

[0026] The mass fraction of the potassium permanganate solution in this embodiment is 5-7%.

[0027] Example 1. A method for producing a circuit board in this embodiment includes the following steps: Step 1: The surface of the copper substrate is provided with an improved layer and a copper foil layer in sequence, and then the substrate covered with the improved layer and the copper foil layer is subjected to hot pressing at a temperature of 180° C. for 2 hours; The improved layer comprises the following raw materials in parts by weight: 50 parts of epoxy resin, 5 parts of modified filler, 4 parts of nano titanium dioxide regulator, and 4 parts of curing agent; The epoxy resin, the modified filler, the nano titanium dioxide regulator and the curing agent are mixed evenly to obtain an improved material, and the improved material is coated on the surface of the copper substrate to form an improved layer; Step 2: 3 parts of 5% sodium citrate solution, 2 parts of 2% chitosan solution and 1 part of silane coupling agent KH560 are mixed evenly to obtain a treatment solution; Step 3: The product of step 1 is immersed in a sufficient amount of treatment liquid, the immersion pressure is 10Mpa, the immersion is 1h, and after the immersion is completed, it is dried to obtain the circuit board of the present invention.

[0028] The thickness of the improved layer of this embodiment is 80um; the thickness of the copper foil layer is 20um; the epoxy resin is a mixture of bisphenol A epoxy resin and phenolic epoxy resin in a weight ratio of 2:1; and the curing agent is 2-phenylimidazole.

[0029] The preparation method of the modified filler of this embodiment is: S01: Silane coupling agent KH550, ethanol and water are mixed in a weight ratio of 2:5:1 to obtain a silane solution; 2 parts of modified boron nitride whiskers, 3 parts of silane solution and 1 part of urea solution are mixed to obtain a modified solution; S02: preheating the nano-attapulgite at 62° C. for 1 h, and then stirring the preheated nano-attapulgite in a modification liquid 3 times the total amount of the preheated nano-attapulgite for modification treatment, and completing the stirring to obtain modified nano-attapulgite; S03: 3 parts of glass fiber, 2 parts of cerium oxide and 4 parts of sodium silicate solution are stirred and mixed thoroughly, then filtered and dried, and then calcined at 150°C for 1 hour. After the calcination is completed, a filler additive is obtained; S04: The modified nano-attapulgite and the filler additive are mixed and ball-milled in a weight ratio of 5:3. After the ball-milling is completed, the mixture is filtered and dried to obtain a modified filler.

[0030] The mass fraction of the urea solution in this embodiment is 2%; the stirring speed of the stirring modification treatment is 450 r / min, and the stirring is for 1 hour.

[0031] The mass fraction of the sodium silicate solution in this embodiment is 3%.

[0032] The preparation method of the modified boron nitride whisker of this embodiment is: 4 parts of boron nitride whiskers and 1 part of nano-silica sol are added to 5 parts of sodium lignin sulfonate solution, followed by adding 2 parts of silicon carbide powder and 1 part of lanthanum oxide, and then mixing and ball milling are performed. After the ball milling is completed, the modified boron nitride whiskers are obtained by suction filtration and drying.

[0033] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 2%; the ball milling speed of the mixing ball milling treatment is 1050r / min, and the ball milling is performed for 1h.

[0034] The preparation method of the nano titanium dioxide regulator of this embodiment is: S101: Mix nano titanium dioxide in a sufficient amount of potassium permanganate solution and mix well, then wash, filter and dry; S102: stirring and adjusting the dried nano titanium dioxide and the adjusting liquid in a weight ratio of 2:5, filtering and drying after the stirring is completed, to obtain a nano titanium dioxide adjusting agent; The preparation method of the regulating solution is as follows: 2 parts of hydroxyapatite, 1 part of alginate, and 1 part of calcium stearate are added to 3 parts of 5% by mass sodium dodecylbenzene sulfonate solution and stirred evenly to obtain the regulating solution.

[0035] The stirring speed of the stirring adjustment process in this embodiment is 550 r / min, and the stirring is performed for 1 hour.

[0036] The mass fraction of the potassium permanganate solution in this embodiment is 5%.

[0037] Example 2. A method for producing a circuit board in this embodiment includes the following steps: Step 1: The surface of the copper substrate is provided with an improved layer and a copper foil layer in sequence, and then the substrate covered with the improved layer and the copper foil layer is subjected to hot pressing at a temperature of 180° C. for 2 hours; The improved layer comprises the following raw materials in parts by weight: 55 parts of epoxy resin, 8 parts of modified filler, 7 parts of nano titanium dioxide regulator, and 7 parts of curing agent; The epoxy resin, the modified filler, the nano titanium dioxide regulator and the curing agent are mixed evenly to obtain an improved material, and the improved material is coated on the surface of the copper substrate to form an improved layer; Step 2: 5 parts of 5% by mass sodium citrate solution, 4 parts of 2% by mass chitosan solution and 3 parts of silane coupling agent KH560 are mixed evenly to obtain a treatment solution; Step 3: The product of step 1 is immersed in a sufficient amount of treatment liquid, the immersion pressure is 10Mpa, the immersion is 1h, and after the immersion is completed, it is dried to obtain the circuit board of the present invention.

[0038] The thickness of the improved layer of this embodiment is 80um; the thickness of the copper foil layer is 20um; the epoxy resin is a mixture of bisphenol A epoxy resin and phenolic epoxy resin in a weight ratio of 2:1; and the curing agent is 2-phenylimidazole.

[0039] The preparation method of the modified filler of this embodiment is: S01: silane coupling agent KH550, ethanol and water are mixed in a weight ratio of 2:5:1 to obtain a silane solution; 4 parts of modified boron nitride whiskers, 5 parts of silane solution and 3 parts of urea solution are mixed to obtain a modified solution; S02: preheating the nano-attapulgite at 66° C. for 1 hour, and then stirring the preheated nano-attapulgite in a modification liquid of 5 times the total amount of the preheated nano-attapulgite for modification treatment, and completing the stirring to obtain modified nano-attapulgite; S03: 5 parts of glass fiber, 3 parts of cerium oxide and 7 parts of sodium silicate solution were stirred and mixed thoroughly, then filtered and dried, and then calcined at 170°C for 1 hour. After the calcination was completed, a filler additive was obtained; S04: The modified nano-attapulgite and the filler additive are mixed and ball-milled in a weight ratio of 5:3. After the ball-milling is completed, the mixture is filtered and dried to obtain a modified filler.

[0040] The mass fraction of the urea solution in this embodiment is 5%; the stirring speed of the stirring modification treatment is 550 r / min, and the stirring is for 1 hour.

[0041] The mass fraction of the sodium silicate solution in this embodiment is 6%.

[0042] The preparation method of the modified boron nitride whisker of this embodiment is: 7 parts of boron nitride whiskers and 3 parts of nano-silica sol are added to 8 parts of sodium lignin sulfonate solution, followed by adding 3 parts of silicon carbide powder and 3 parts of lanthanum oxide, and then mixing and ball milling are performed. After the ball milling is completed, the modified boron nitride whiskers are obtained by filtration and drying.

[0043] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 5%; the ball milling speed of the mixing ball milling treatment is 1150r / min, and the ball milling is 1h.

[0044] The preparation method of the nano titanium dioxide regulator of this embodiment is: S101: Mix nano titanium dioxide in a sufficient amount of potassium permanganate solution and mix well, then wash, filter and dry; S102: stirring and adjusting the dried nano titanium dioxide and the adjusting liquid in a weight ratio of 2:5, filtering and drying after the stirring is completed, to obtain a nano titanium dioxide adjusting agent; The preparation method of the regulating solution is as follows: 4 parts of hydroxyapatite, 3 parts of alginate, and 2 parts of calcium stearate are added to 6 parts of 5% by mass sodium dodecylbenzene sulfonate solution and stirred evenly to obtain the regulating solution.

[0045] The stirring speed of the stirring adjustment process in this embodiment is 750 r / min, and the stirring is performed for 1 hour.

[0046] The mass fraction of the potassium permanganate solution in this embodiment is 7%.

[0047] Example 3. A method for producing a circuit board in this embodiment includes the following steps: Step 1: The surface of the copper substrate is provided with an improved layer and a copper foil layer in sequence, and then the substrate covered with the improved layer and the copper foil layer is subjected to hot pressing at a temperature of 180° C. for 2 hours; The improved layer comprises the following raw materials in parts by weight: 52.5 parts of epoxy resin, 6.5 parts of modified filler, 5.5 parts of nano titanium dioxide regulator, and 5.5 parts of curing agent; The epoxy resin, the modified filler, the nano titanium dioxide regulator and the curing agent are mixed evenly to obtain an improved material, and the improved material is coated on the surface of the copper substrate to form an improved layer; Step 2: Step 2: Blend 4 parts of 5% sodium citrate solution, 3 parts of 2% chitosan solution and 2 parts of silane coupling agent KH560 to obtain a treatment solution; Step 3: The product of step 1 is immersed in a sufficient amount of treatment liquid, the immersion pressure is 10Mpa, the immersion is 1h, and after the immersion is completed, it is dried to obtain the circuit board of the present invention.

[0048] The thickness of the improved layer of this embodiment is 80um; the thickness of the copper foil layer is 20um; the epoxy resin is a mixture of bisphenol A epoxy resin and phenolic epoxy resin in a weight ratio of 2:1; and the curing agent is 2-phenylimidazole.

[0049] The preparation method of the modified filler of this embodiment is: S01: Silane coupling agent KH550, ethanol and water are mixed in a weight ratio of 2:5:1 to obtain a silane solution; 3 parts of modified boron nitride whiskers, 4 parts of silane solution and 2 parts of urea solution are mixed to obtain a modified solution; S02: preheating the nano-attapulgite at 64° C. for 1 hour, and then stirring the preheated nano-attapulgite in a modification liquid of 4 times the total amount of the preheated nano-attapulgite for modification treatment, and completing the stirring to obtain modified nano-attapulgite; S03: 4 parts of glass fiber, 2.5 parts of cerium oxide and 5.5 parts of sodium silicate solution were stirred and mixed thoroughly, then filtered and dried, and then calcined at 160° C. for 1 hour. After the calcination was completed, a filler additive was obtained; S04: The modified nano-attapulgite and the filler additive are mixed and ball-milled in a weight ratio of 5:3. After the ball-milling is completed, the mixture is filtered and dried to obtain a modified filler.

[0050] The mass fraction of the urea solution in this embodiment is 3.5%; the stirring speed of the stirring modification treatment is 500 r / min, and the stirring is for 1 hour.

[0051] The mass fraction of the sodium silicate solution in this embodiment is 4.5%.

[0052] The preparation method of the modified boron nitride whisker of this embodiment is: 5.5 parts of boron nitride whiskers and 2 parts of nano-silica sol are added to 6.5 parts of sodium lignin sulfonate solution, followed by adding 2.5 parts of silicon carbide powder and 2 parts of lanthanum oxide, and then mixing and ball milling. After the ball milling is completed, the modified boron nitride whiskers are obtained by suction filtration and drying.

[0053] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 3.5%; the ball milling speed of the mixing ball milling treatment is 1100 r / min, and the ball milling is performed for 1 hour.

[0054] The preparation method of the nano titanium dioxide regulator of this embodiment is: S101: Mix nano titanium dioxide in a sufficient amount of potassium permanganate solution and mix well, then wash, filter and dry; S102: stirring and adjusting the dried nano titanium dioxide and the adjusting liquid in a weight ratio of 2:5, filtering and drying after the stirring is completed, to obtain a nano titanium dioxide adjusting agent; The preparation method of the regulating solution is as follows: 3 parts of hydroxyapatite, 2 parts of alginate, and 1.5 parts of calcium stearate are added to 4.5 parts of 5% by mass sodium dodecylbenzene sulfonate solution and stirred evenly to obtain the regulating solution.

[0055] The stirring speed of the stirring adjustment process in this embodiment is 600 r / min, and the stirring is performed for 1 hour.

[0056] The mass fraction of the potassium permanganate solution in this embodiment is 6%.

[0057] Comparative Example 1. The difference from Example 3 is that no modified filler is added.

[0058] Comparative Example 2. The difference from Example 3 is that no modified nano-attapulgite is added in the preparation of the modified filler.

[0059] Comparative Example 3. The difference from Example 3 is that no modifying liquid is added in the preparation of the modified nano-attapulgite.

[0060] Comparative Example 4. The difference from Example 3 is that no modified boron nitride whiskers are added to the modified solution.

[0061] Comparative Example 5. The difference from Example 3 is that no filler auxiliary agent is added in the preparation of the modified filler.

[0062] Comparative Example 6. The difference from Example 3 is that no glass fiber is added in the preparation of the filler additive.

[0063] Comparative Example 7. The difference from Example 3 is that no cerium oxide is added in the preparation of the filler additive.

[0064] Comparative Example 8. The difference from Example 3 is that no nano titanium dioxide regulator is added.

[0065] Comparative Example 9. The difference from Example 3 is that no conditioning liquid is added to the nano titanium dioxide conditioning agent.

[0066] Comparative Example 10. The difference from Example 3 is that hydroxyapatite and alginate are not added to the conditioning solution.

[0067] The improved layers in the products of Examples 1 to 3 and Comparative Examples 1 to 10 were subjected to conventional performance tests, including thermal conductivity, dielectric loss and wear resistance, and product stability under high heat and high humidity conditions (the products were placed at 75° C. and 45% humidity for 48 hours to test the performance stability of the products). The test results are as follows:

[0068] It can be seen from Comparative Examples 1-10 and Examples 1-3 and stability tests that; The product of Example 3 has excellent thermal conductivity, dielectric loss and wear resistance, and the three properties can be improved in a coordinated manner. The product has a significant effect on product stability under high heat and high humidity conditions, and the product's performance stability has a significant improvement effect. The present invention does not add any of the modified fillers and the nano titanium dioxide regulators, and the performance stability of the product shows a significant trend of deterioration. The coordination and synergy of the two are adopted to achieve the most significant performance effect of the product. The performance of the products showed a trend of deterioration to varying degrees when no modified nano-attapulgite was added to the preparation of the modified filler, no modifying liquid was added to the preparation of the modified nano-attapulgite, no modified boron nitride whiskers were added to the modifying liquid, no filler additive was added to the preparation of the modified filler, no glass fiber was added to the preparation of the filler additive, and no cerium oxide was added to the preparation of the filler additive. The performance of the modified filler prepared by combining the modified nano-attapulgite obtained by the specific method of the present invention with a specific filler additive was the most significant. Other methods were not as significant as the effect of the present invention. The inventors of the present invention also found that the performance of the product deteriorated significantly when no modified boron nitride whiskers were added to the modifying liquid. The performance of the product also showed a trend of deterioration when no conditioning liquid was added to the nano-titanium dioxide conditioning agent, and hydroxyapatite and alginate were not added to the conditioning liquid. The nano-titanium dioxide conditioning agent prepared by the conditioning liquid obtained by the specific method of the present invention had the most significant product performance effect.

[0069] The present invention further explores the product performance through the preparation of modified boron nitride whiskers; Experimental example 1. The only difference from Example 3 is that no boron nitride whiskers are added in the preparation of the modified boron nitride whiskers.

[0070] Experimental example 2. The only difference from Example 3 is that silicon carbide powder is not added in the preparation of modified boron nitride whiskers.

[0071] Experimental Example 3. The only difference from Example 3 is that lanthanum oxide is not added in the preparation of the modified boron nitride whiskers.

[0072] Experimental Example 4. The only difference from Example 3 is that no nano-silica sol is added in the preparation of the modified boron nitride whiskers.

[0073] Experimental Example 5. The only difference from Example 3 is that the sodium lignin sulfonate solution is replaced by water.

[0074] Taking the product under high heat and high humidity conditions as an example, the performance test was conducted and its performance was tested as follows;

[0075] It can be seen from Experimental Examples 1-5 that no boron nitride whisker is added in the preparation of the modified boron nitride whisker, and the performance of the product changes under normal conditions. Among the preparation factors of the modified boron nitride whisker, the performance deterioration is the most obvious. At the same time, no silicon carbide powder is added in the preparation of the modified boron nitride whisker, and the performance of the product deteriorates most obviously under the stability test. Silicon carbide powder and boron nitride whisker are used in the preparation of the modified boron nitride whisker to enhance the performance effect of the product. At the same time, no lanthanum oxide is added in the preparation of the modified boron nitride whisker, no nano-silica sol is added in the preparation of the modified boron nitride whisker, and water is used instead of sodium lignin sulfonate solution. The performance of the product has a tendency to deteriorate. Only the modified boron nitride whisker obtained by the method of the present invention has the best product performance effect, and the conditions for adjusting the preparation of boron nitride whiskers of the present invention are unique. The modified boron nitride whiskers prepared by other methods are not as significant as the effect of the present invention.

[0076] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0077] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for producing a circuit board, characterized in that: The following steps are involved: Step 1: The surface of the copper substrate is provided with an improved layer and a copper foil layer in sequence, and then the substrate covered with the improved layer and the copper foil layer is subjected to hot pressing at a temperature of 180° C. for 2 hours; The improved layer comprises the following raw materials in parts by weight: 50-55 parts of epoxy resin, 5-8 parts of modified filler, 4-7 parts of nano titanium dioxide regulator, and 4-7 parts of curing agent; The epoxy resin, the modified filler, the nano titanium dioxide regulator and the curing agent are mixed evenly to obtain an improved material, and the improved material is coated on the surface of the copper substrate to form an improved layer; Step 2: 3-5 parts by mass of 5% sodium citrate solution, 2-4 parts by mass of 2% chitosan solution and 1-3 parts by mass of silane coupling agent KH560 are uniformly mixed to obtain a treatment solution; Step 3: The product of step 1 is immersed in a sufficient amount of treatment liquid, the immersion pressure is 10Mpa, the immersion is 1h, and after the immersion is completed, it is dried to obtain the circuit board of the present invention.

2. A method for producing a circuit board according to claim 1, characterized in that: The thickness of the improved layer is 80um; the thickness of the copper foil layer is 20um; the epoxy resin is prepared by bisphenol A epoxy resin and phenolic epoxy resin in a weight ratio of 2:1; and the curing agent is 2-phenylimidazole.

3. A method for producing a circuit board according to claim 1, characterized in that: The preparation method of the modified filler is: S01: silane coupling agent KH550, ethanol and water are mixed in a weight ratio of 2:5:1 to obtain silane liquid; 2-4 parts of modified boron nitride whiskers, 3-5 parts of silane solution and 1-3 parts of urea solution are uniformly mixed to obtain a modified solution; S02: preheating the nano-attapulgite at 62-66° C. for 1 hour, and then stirring the preheated nano-attapulgite in a modification liquid that is 3-5 times the total amount of the preheated nano-attapulgite for modification treatment, and completing the stirring to obtain modified nano-attapulgite; S03: 3-5 parts of glass fiber, 2-3 parts of cerium oxide and 4-7 parts of sodium silicate solution are stirred and mixed thoroughly, then filtered and dried, and then calcined at 150-170°C for 1 hour. After the calcination is completed, a filler additive is obtained; S04: The modified nano-attapulgite and the filler additive are mixed and ball-milled in a weight ratio of 5:

3. After the ball-milling is completed, the mixture is filtered and dried to obtain a modified filler.

4. A method for producing a circuit board according to claim 3, characterized in that: The mass fraction of the urea solution is 2-5%; the stirring speed of the stirring modification treatment is 450-550r / min, and the stirring is for 1h.

5. A method for producing a circuit board according to claim 3, characterized in that: The mass fraction of the sodium silicate solution is 3-6%.

6. A method for producing a circuit board according to claim 3, characterized in that: The preparation method of the modified boron nitride whisker is: 4-7 parts of boron nitride whiskers and 1-3 parts of nano-silica sol are added to 5-8 parts of sodium lignin sulfonate solution, followed by adding 2-3 parts of silicon carbide powder and 1-3 parts of lanthanum oxide, and then mixing and ball milling. After the ball milling is completed, the modified boron nitride whiskers are obtained by suction filtration and drying.

7. A method for producing a circuit board according to claim 6, characterized in that: The mass fraction of the sodium lignin sulfonate solution is 2-5%; the ball milling speed of the mixing ball milling treatment is 1050-1150r / min, and the ball milling is for 1h.

8. The method for producing a circuit board according to claim 1, characterized in that: The preparation method of the nano titanium dioxide regulator is: S101: Mix nano titanium dioxide in a sufficient amount of potassium permanganate solution and mix well, then wash, filter and dry; S102: stirring and adjusting the dried nano titanium dioxide and the adjusting liquid in a weight ratio of 2:5, filtering and drying after the stirring is completed, to obtain a nano titanium dioxide adjusting agent; The preparation method of the regulating solution is as follows: 2-4 parts of hydroxyapatite, 1-3 parts of alginate, and 1-2 parts of calcium stearate are added to 3-6 parts of 5% by mass sodium dodecylbenzene sulfonate solution and stirred evenly to obtain the regulating solution.

9. A method for producing a circuit board according to claim 8, characterized in that: The stirring speed of the stirring adjustment treatment is 550-750 r / min, and the stirring is performed for 1 hour.

10. A method for producing a circuit board according to claim 8, characterized in that: The mass fraction of the potassium permanganate solution is 5-7%.

Citation Information

Patent Citations

  • Composite build-up material for embedding of circuitry

    CN103141163A

  • Organic silicon resin composition and prepreg, laminated board, copper-clad plate and aluminum-based plate adopting same

    CN105778506A

  • Method for preparing insulated electronic material for high frequency circuit board

    CN109206852A

  • Aerogel insulation panel and manufacturing method thereof

    CN116469626A

  • Glue composition for copper-clad plate and preparation method thereof

    CN118667491A

Cited By

  • Knitted fabric for temperature-controllable underwear and preparation method thereof

    CN120625255A

  • Knitted fabric for temperature-controllable underwear and method for manufacturing the same

    CN120625255B